Gambaran Peresepan Obat Anti Inflamasi Pada Pasien Rawat Jalan di Klinik dan Apotek Erick Atdoctor Dumai - Mevy Trisna; Renatalia Fika; Ayu Noviyola; Muhajri Agusfina; Trie Yuni Elfasyari (Program Studi S1 Farmasi, STIKES Senior, Medan, 2026)
Inflammation is a response to tissue injury or infection. It is characterized by redness, heat, swelling, and pain. Anti-inflammatory drugs are drugs or classes of drugs that suppress or reduce inflammation. Anti-inflammatory drugs are divided into two groups: steroidal anti-inflammatory drugs and non-steroidal anti-inflammatory drugs. Anti-inflammatory drug prescriptions at Erick Atdoctor Clinic & Pharmacy are classified as fast-moving. The purpose of this study was to determine the description of anti-inflammatory drug prescriptions among outpatients at Erick Atdoctor Clinic & Pharmacy in Dumai based on age, gender, drug type, and anti-inflammatory drug class. The research method is descriptive with a quantitative approach, with retrospective data collection and observational data collection. Secondary data were anti-inflammatory prescriptions from outpatients in the General Clinic for February–December 2024. The population obtained was 205 prescriptions, and the sampling method used was purposive sampling. A total of 136 prescriptions met the inclusion and exclusion criteria. Data analysis used univariate analysis to describe the characteristics of each research variable by calculating the frequency and percentage of each variable studied. Based on the research results, the most frequently prescribed medications were found in the 26-35 age group (44 prescriptions) (32.35%), male (75 prescriptions) (55.15%), and the types of medications were monotherapy (117 prescriptions) (86.03%), steroidal anti-inflammatory monotherapy (32.48%), and mefenamic acid (17.95%) (21 prescriptions). The most commonly prescribed combination therapy was methylprednisolone and Ibuprofen (42.11%), with 8 prescriptions. The most commonly prescribed anti-inflammatory drug class was steroidal anti-inflammatory drugs (51.28%), with 60 prescriptions.